The Influence of Fenugreek Seed Powder Addition on the Nutritional, Antioxidant, and Sensorial Properties of Value-Added Noodles - Zulfiqar Ahmad; Muhammad Ilyas; Kashif Ameer; Muhammad Asif Khan; Muhammad Waseem; Faiz-ul-Hassan Shah; Tahir Mehmood; Muhammad Adil Rehman; Isam A. Mohamed Ahmed (Journal of Food Quality)
The present study aimed at assessing the nutritional, antioxidant, and sensorial attributes of fenugreek seed powder (FSP) and supplemented functional noodles prepared by replacing wheat flour at 2–10% supplementation levels. Cooking losses of the value-added baked goods significantly (p<0.05) declined from 2.4–1.2%. The results for water solubility, foaming capacity, and bulk density suggested significant (p<0.05) increases from 8–10%, 77–87% and 0.51–0.70 g/mL, respectively, on replacing wheat flour with FSP in the value-added product. Dehydrated FSP addition caused significant (p<0.05) improvement in ash (0.90–1.54%), proteins (10.4–13.7%), and crude fibers (0.9–1.9%) contents of the noodles. Maximum supplementation of FSP in supplemented noodles significantly (p<0.05) improved the TPC, TFC, DPPH, and FRAP values from 111–310 mg GAE/100 g, 2.3–2.8 mg CE/g, 31–42%, and 215–460 umol/100 g, respectively. Sensory evaluation of supplemented noodles revealed the highest sensory acceptability of the value-added product at a 6% supplementation level. Conclusively, supplementing dehydrated FSP in the development of value-added foods could improve its functional features. It could also be considered as a plausible source of fibers and proteins, which might be helpful in mitigating malnutrition and a number of health maladies, such as cancer and diabetes.